THE IMPACT OF FOREIGN JOINT VENTURES ON THE INFRASTRUCTURE DEVELOPMENT OF SIRDARYO REGION (Web of Teachers: Inderscience Research, 2026)
This scientific article analyzes the impact of foreign joint ventures on the development of infrastructure in the Sirdaryo region of the Republic of Uzbekistan. The study examines the role of foreign-participated enterprises in the modernization of transport, energy, industrial, and social infrastructure, as well as their contribution to regional economic integration. Based on official statistical reports, government programs, and analytical studies, the article highlights how foreign investment has influenced infrastructural transformation processes in the region since the period of economic reforms.